Alcohol Use Before Sexual Violence and Cognitive Appraisals: Differential Associations With Barriers to Help-Seeking - Brockdorf, Alexandra N. (Violence against women, 2023)
The current study examined two cognitive appraisals—labeling (identifying an unwanted sexual experience as sexual violence) and self-blame—as potential mechanisms between survivor alcohol use before sexual violence and three help-seeking barriers (minimization, negative treatment, and social-emotional barriers) among non-service-seeking sexual violence survivors. Participants were 141 undergraduate women who completed self-report measures. Three parallel mediation models were tested. Survivors who were drinking were more likely to label their victimization as sexual violence and, in turn, perceived fewer minimization and greater social-emotional barriers. Further, survivors who were drinking blamed themselves more and, in turn, perceived greater negative treatment and social-emotional barriers.